Ação da supervisão de ensino paulista: legal-racional e patrimonialista - Piccoli, Denise Fujihara (Universidade Federal de São Carlos, 2019)
This research aims at analysing the teaching supervisor actions at the State Department of Education of the State of São Paulo. The position of teaching supervisor is the one which, since its origin, would be in charge of guaranteeing the actions standardization of the actions of the teaching system as well as eliminating the local practices which still show a patrimonial character by law enforcement and monitoring. This research is based on the theoretical framework developed by Max Weber. The main purpose of this study is to understand the activities developed by the teaching supervisor at the State Department of Education of the State of São Paulo from 2012 to 2016. To achieve this goal, five attributions of the teaching supervisor will be analysed: 1) the provision of classes for hired teachers; 2) recruitment of teaching coordinators for the Pedagogical Area; 3) recruitment of school principals to work at schools which participate in the “Integral Education Program”; 4) the transference process of the teaching supervisor, and 5) the process of substitution of the teaching supervisor. We also aim at identifying the possibility of the presence of traditional elements resulted from a patrimonial legacy originated from the formation of the Brazilian State and the rational elements introduced in the nineteenth century. Our purpose is to understand the practices of this professional, whose function, among others, is to guide and supervise others in terms of their adherence to the guidelines, seeking to standardize the procedures and to eliminate individual interferences. To achieve this goal, this paper analyse the Federal Register of São Paulo and information from people whose function are listed above was collected. It is observed that, even today, the actions of teaching supervisor has not been able to guarantee that local actions follow the same principle in every educational system nor succeed in the annulment of patrimonialist practices.
Action of teaching supervision: legal-rational and patrimonialist
Keywords: Supervisão de Ensino; Legal- racional; Patrimonialismo; Teaching supervision; Legal-rational; Patrimonialism; CIENCIAS HUMANAS::EDUCACAO